Electric Cupping Therapy for Stress Reduction in Patients with Hypertension: A Quasi-Experimental Study - Sri Handayani; Wijayanti Wijayanti; Pandu Aseta (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Hypertension is a major public health problem that is frequently associated with psychological stress, which may adversely affect overall well-being and disease management. Complementary interventions that support stress reduction may therefore contribute to more holistic hypertension care. This study aimed to evaluate the effect of controlled electric cupping therapy on perceived stress among patients with hypertension. Method: A quasi-experimental study employing a one-group pre–posttest design was conducted among 39 patients with primary hypertension at Rumah Bekam Salim Karanganyar. Participants received a single session of electric cupping therapy using a standardized pressure setting of 250 mmHg. Perceived stress was assessed using the Perceived Acute Stress Scale-10 (PASS-10). Data normality was evaluated using the Shapiro–Wilk test, and pre–post differences were analyzed using a paired-samples t-test. Result: The mean PASS-10 score decreased from 23.69 ± 6.02 before the intervention to 12.74 ± 4.49 after the intervention. Statistical analysis demonstrated a significant reduction in perceived stress following electric cupping therapy (t(38) = 28.69, p < 0.001), with a very large effect size (Cohen’s d = 4.59). Conclusion: The findings suggest that controlled electric cupping therapy may have potential as a complementary approach for reducing perceived stress among patients with hypertension. However, because the study employed a one-group pre–posttest design without a control group, the results should be interpreted as preliminary. Further randomized controlled studies are needed to confirm these findings and determine the intervention’s effectiveness.